The effect of the Other 3Rs program on the social skills of Lebanese middle school students - Jawad, Wafa Hussein (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2001)
This study examined the effect of an intervention, namely the 3Rs program, on the social skills of Lebanese middle school students.--The sample was 2 sections of a class of 7th grade students in a private school in Sidon, Lebanon. Over a period of six weeks, students in the experimental group (n=21) were exposed to selected activities from the Other 3Rs program, whereas students in the control group (n=20) were doing reading exercises.--A behavior checklist and the BarOn EQ-i:YV inventory were used to measure certain social skills and certain character traits related to emotional intelligence. Separate analyses of variance were used to check for initial and post training differences between the two groups on each of the checklist and the BarOn inventory.--The results show a significant decrease in the average frequency of negative behaviors in the experimental group, but the results did not show any statistically significant change in the frequency of the positive behaviors nor in the scores on the BarOn inventory. The results were discussed and recommendations for further research were proposed.
: Mémoire
Keywords: Comportement Social; Cycle moyen; Intermediate Education; Intervention Programs; Programme des interventions; Social Behavior